181 Developing educational package on child injury prevention mobilising womens' groups in rural nepal. (1st September 2016) - Pant, Puspa Raj; Ellis, Matthew; Deave, Toity; Mytton, Julie
Abstract : Background: Non-fatal injuries are many times more common than fatal injuries and may lead to lifelong consequences in children. Lack of child injury surveillance system hinders evidence generation in a low-income setting. Children in rural Nepal are exposed to widespread injury risks and families may have little awareness of how they can be prevented. Community mobilisation may be an effective approach. This study aimed to develop an educational package on child injury prevention and assess the feasibility of delivering it with the involvement of women's groups. Methods: An educational package was developed for Female Community Health Volunteers (FCHVs) that included both primary and secondary prevention materials for unintentional child injuries and was adapted from those developed by CIPRB (Bangladesh). Ten women's groups across 9 wards in one village development committee (VDC) area were actively engaged in 6 monthly meetings. The sessions were led by FCHV and lasted for 1–2 hours where rigorous discussions were held using the educational materials provided. Structured checklists were used to obtain feedback and to assess the delivery and reach of the programme. Results: First-aid training, meeting faciliation guide, parents' booklet and educational wall posters were the major outputs of this project. Nine FCHVs received first-aid training and kits. FCHVs convened 10 women's groups to run over 6 months with 25 to 30 mothers attending each session. Each group presented their views on child injury risks and proposed prevention activities at local public meetings. Community members appreciated the project and developed their own interventions to tackle local injury hazards. Conclusions: It is feasible to develop and implement a community mobilisation intervention where women's groups work with FCHVs to prevent injuries in children. The intervention was well received by the women's groups and by community members.